2007
DOI: 10.1590/s0034-72992007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Manobra de Epley repetida em uma mesma sessão na vertigem posicional paroxística benigna

Abstract: Aim: To assess whether more than one Epley's maneuver in the same session, compared to a single one, decreases the number of sessions necessary to suppress positional nystagmus. Method: Epley's maneuver was done in 123 patients with BPPV due to unilateral posterior semicircular canal canalolithiasis. The number of sessions for positional nystagmus suppression was compared in two groups of patients. Group I consisted of 75 patients submitted to a single Epley's maneuver on weekly sessions and group II consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Korn et al 25 and Dorigueto et al 26 studied the number of maneuvers which must be used to treat BPPV and concluded that repeated maneuvers in the same session seem to be more efficient, and even more necessary when one is dealing with cupulolithiasis. It was only in one of the studies 19 hereby analyzed, that it was not possible to identify a specific number or a protocol for such, and the CR repetition must be determined by symptom severity, if persistent, by the professional's evaluation and its successful treatment with the maneuver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Korn et al 25 and Dorigueto et al 26 studied the number of maneuvers which must be used to treat BPPV and concluded that repeated maneuvers in the same session seem to be more efficient, and even more necessary when one is dealing with cupulolithiasis. It was only in one of the studies 19 hereby analyzed, that it was not possible to identify a specific number or a protocol for such, and the CR repetition must be determined by symptom severity, if persistent, by the professional's evaluation and its successful treatment with the maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…Based on two class i studies, three class ii, four metanalysis and one systematic review, Fife et al 18 classified the maneuver as "Level A recommendation", in other words, treatment is effective and safe, and it should be offered to the patients of all ages with posterior canal BppV. korn et al 25 and dorigueto et al 26 studied the number of maneuvers which must be used to treat BppV and concluded that repeated maneuvers in the same session seem to be more efficient, and even more necessary when one is dealing with cupulolithiasis. it was only in one of the studies 19 hereby analyzed, that it was not possible to identify a specific number or a protocol for such, and the Cr repetition must be determined by symptom severity, if persistent, by the professional's evaluation and its successful treatment with the maneuver.…”
Section: Canal Repositioning Maneuvermentioning
confidence: 99%